Literasi Media Digital Canva Mahasiswa dalam Menyusun Materi Pembelajaran Bahasa Indonesia - Juanda*, Juanda; Mansur, Umar; R, Mantasiah (Alinea: Jurnal Bahasa, Sastra, dan Pengajaran, 2025)
This study aims to measure the level of digital literacy of students using Canva in preparing Indonesian learning materials. The research used a quantitative approach with a descriptive survey method, involving respondents from students of the Indonesian Language and Literature Education Study Program, Universitas Muslim Indonesia. The results showed that the overall level of digital literacy of students was classified as moderate with an average score of 68.5/100. In the aspect of technical ability, 65% of students were at an intermediate level, but only 10% mastered Canva's advanced features. In design creativity, 45% of students showed moderate ability, while 30% were in the high category. As many as 75% of students were able to adapt the design to learning needs, although only 20% showed in-depth mastery. In addition, 70% of students found Canva helpful in creating interesting and easy-to-understand materials. These results make a significant contribution to the development of technology-based education curriculum for higher education. This study recommends project-based digital literacy training, as well as faculty and student collaboration to improve digital literacy. Future research should expand the sample, use mixed-methods for more in-depth analysis, and explore other dimensions of digital literacy.Keywords: Canva; digital literacy; media; learning technologyAbstrakPenelitian ini bertujuan mengukur tingkat literasi digital mahasiswa menggunakan Canva dalam menyusun materi pembelajaran bahasa Indonesia. Penelitian menggunakan pendekatan kuantitatif dengan metode survei deskriptif, dengan melibatkan responden dari mahasiswa Program Studi Pendidikan Bahasa dan Sastra Indonesia, Universitas Muslim Indonesia. Hasil penelitian menunjukkan tingkat literasi digital mahasiswa secara keseluruhan tergolong sedang dengan rata-rata skor 68,5/100. Pada aspek kemampuan teknis, 65% mahasiswa berada pada tingkat menengah, namun hanya 10% yang menguasai fitur lanjutan Canva. Dalam kreativitas desain, 45% mahasiswa menunjukkan kemampuan sedang, sementara 30% berada pada kategori tinggi. Sebanyak 75% mahasiswa mampu menyesuaikan desain dengan kebutuhan pembelajaran, meskipun hanya 20% yang menunjukkan penguasaan mendalam. Selain itu, 70% mahasiswa merasa Canva membantu menciptakan materi yang menarik dan mudah dipahami. Penelitian ini merekomendasikan pelatihan literasi digital berbasis proyek, serta kolaborasi dosen dan mahasiswa untuk meningkatkan literasi digital. Untuk penelitian ke depan disarankan memperluas sampel, menggunakan metode mixed-methods untuk analisis yang lebih mendalam, serta mengeksplorasi dimensi literasi digital lainnya.Katakunci: Canva; literasi digital; media; teknologi pembelajaran